1990
DOI: 10.1111/j.1476-5381.1990.tb15833.x
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of the adenosine receptor in porcine coronary arteries

Abstract: 1 Relaxant responses of ring preparations from porcine ventricular coronary arteries to adenosine and various stable adenosine analogues were investigated in vitro. 2 The adenosine analogues did not produce contraction but elicited almost complete relaxation of coronary arteries preconstricted with 3 pJm prostaglandin F2 (PGF2z), even after removal of the endothelium.3 The order of potency, was 5'-N-ethylcarboxamide-adenosine (NECA) > 242-phenylethylamino)5'-adenosine (CPA) > adenosine > ATP = ADP which sugges… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
23
0

Year Published

1992
1992
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(27 citation statements)
references
References 13 publications
3
23
0
Order By: Relevance
“…This study also showed that contractile responses of human coronary arteries to α,β-meATP and the stable pyrimidine analogue, uridine 5′-O-3-thiotriphosphate, were consistent with activation of P2X1R and P2Y2R, respectively. UTPevoked contractions of porcine coronary artery smooth muscle cells also appear to be mediated predominantly by P2Y2R [422][423][424][425][426]. The adenosine may be released directly from cardiomyocytes and endothelial cells after intra-and extracellular breakdown of ATP, respectively [427].…”
Section: Coronary Blood Vesselsmentioning
confidence: 99%
“…This study also showed that contractile responses of human coronary arteries to α,β-meATP and the stable pyrimidine analogue, uridine 5′-O-3-thiotriphosphate, were consistent with activation of P2X1R and P2Y2R, respectively. UTPevoked contractions of porcine coronary artery smooth muscle cells also appear to be mediated predominantly by P2Y2R [422][423][424][425][426]. The adenosine may be released directly from cardiomyocytes and endothelial cells after intra-and extracellular breakdown of ATP, respectively [427].…”
Section: Coronary Blood Vesselsmentioning
confidence: 99%
“…1991;Fleetwood & Gordon, 1987;Gordon, 1986;Hopwood & Burnstock, 1987;Matsumoto et al, 1997;Olsson & Pearson, 1990;Simonsen et al, 1997;Vials & Burnstock, 1994;Godecke et al, 1996). However, antagonism of ATP-induced coronary vasodilation by AdoR antagonists implicates activation of A 2A -AdoRs in the action of ATP (White & Angus, 1987;Bunger et al, 1975;King et al, 1990;Kroll & Schrader, 1993). Until now the lack of selective and potent antagonists for either P 2Y or A 2A -adenosine receptors has been an obstacle to the identi®cation of the type receptor(s) that mediate ATP-induced coronary vasodilation.…”
Section: Introductionmentioning
confidence: 99%
“…It can arise directly from cardiomyocytes after intracellular breakdown of ATP and after extracellular breakdown of ATP released from endothelial cells (Pekka Raatikainen et al, 1991). It was suggested that the vasodilator actions of adenosine were mediated by A 2 receptors (Leung et al, 1985;Daly et al, 1986;Odawara et al, 1986;see Mustafa et al, 2009), probably located on endothelial cells (Kroll et al, 1987;Des Rosiers and Nees, 1987;Ramagopal et al, 1988a;Balcells et al, 1992;King et al, 1990), perhaps together with another P1 receptor subtype . Methylxanthines antagonized A 2 receptor-mediated coronary vasodilation (Ramagopal Purinergic Signaling and Blood Vessels et al, 1988b).…”
mentioning
confidence: 99%